Finding Like Minds and Gaining Inspiration: A Conversation with Teddie Potter - Riane Eisler (Interdisciplinary Journal of Partnership Studies)
Riane Eisler interviews Dr. Teddie Potter, Co-Founder and Executive Editor of the Interdisciplinary Journal of Partnership Studies and Director of the Center for Planetary Health and Environmental Justice at the University of Minnesota School of Nursing.